Hepatoprotective Activities Of Polar And Non Polar Extract Kembang Sepatu Flower (Hibiscus rosasinensis L.): Hepatoprotective Activities Of Polar And Non Polar Extract Kembang Sepatu Flower (Hibiscus rosasinensis L.) - Adil Ellen Hettie; Nonny Manampiring (Universitas Negeri Manado, 2020)
This study aims to obtain the dominant phytochemical group in polar and non-polar extracts of hibiscus flowers and obtain data on hepatoprotective activity of polar and non-polar extracts of hibiscus flowers on male white rats induced by high doses of paracetamol. This study consists of the stages of extraction, stages phytochemical analysis and test phase of hepatoprotective activity using rat test animals. Treat done is negative control (K -). This group was only given solvents (CMC Na 0.5%) 1ml / head / day for 28 days and was not given heat stress treatment. H0. This group was given solvents (CMC Na 0.5%) 1ml / head / day for 28 days, after which they were given heat stress treatment for eight days. H1 This group was given a polar extract of Hibiscus rosasinensis red flowers at a dose of 0.075g mg / 200gramBB / day in a 0.5% CMC suspension of 1 ml for 14 days, and after that was given heat stress treatment for eight days. H2. This group was given a non-polar extract of Hibiscus rosasinensis red flowers at a dose of 0.075mg / 200gramBB / day in a 1% CMC suspension of 1 ml for 14 days, and after that was given heat stress treatment for eight days. The measured parameters were the content of SGPT and SGOT . The results showed that the polar extract and non-polar extract Hibiscus rosasinensis L. red variety were able to maintain levels of the SGOT and SGPT enzymes in white rats (Rattus norvegicus) induced by high doses of paracetamol, as in the negative control group (K-).